Cultural Sociology of the Middle East, Asia, and Africa IV : an Encyclopedia - South, Central, and West Asia - ELLIOT, Carolyn M. (ed.) (Thousand Oaks:Sage Publications, Inc., 2012)
Koleksi Referensi (Tidak Dipinjamkan)